(untitled) (Nexo Revista Científica, 2021)
New towns and cities are proposed as the places for absorbing the population overflow and limiting the population growth in metropolises. In Iran, these towns and cities are built very close to the metropolises, and gradually, they are being used only as dormitories. The new town of Pardisan is built 13 kilometers southwest of Qom as the largest new town of the urban district of Qom in order to organize the residence system and absorb the population overflow of the metropolis of Qom and reduce its problems. This paper studies the function of the Pardisan new town as the absorber of the population overflow of Qom and also the residents’ satisfaction with this town. The research method adopted by this study is based on the library, documentary, and field data, and also interviews and collection of data by questionnaires and TOPSIS model. The results of this research indicate that many of the families living in the Pardisan town constitute the population overflow of the metropolis of Qom; Among the most important reasons for the migration of families to the Pardisan town is the low cost of land and residence, and 4.67 percent of the residents do not like to live in this town. This unsuccess is mostly due to lack of job and activity in this town, and therefore, the residents are less satisfied with the town.